2014
DOI: 10.1007/s00431-014-2460-x
|View full text |Cite
|
Sign up to set email alerts
|

Motor performance in children and adolescents with cancer at the end of acute treatment phase

Abstract: Overall, motor performance was low in the patient group studied. We recommend that individualized exercise interventions to attenuate motor deficits and promote physical activity are needed during cancer treatment in order to enhance motor performance and improve social participation during and after cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 43 publications
5
47
0
7
Order By: Relevance
“…It is well known that a considerable number of HSCT children already suffer from physical and psychological disabilities due to earlier intensified treatment modalities, social isolation, and inactivity during therapy . Morishita and colleagues showed in a cohort of adult patients that handgrip and knee extension strength as well as submaximal exercise capacity before HSCT were significantly lower than normative values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that a considerable number of HSCT children already suffer from physical and psychological disabilities due to earlier intensified treatment modalities, social isolation, and inactivity during therapy . Morishita and colleagues showed in a cohort of adult patients that handgrip and knee extension strength as well as submaximal exercise capacity before HSCT were significantly lower than normative values.…”
Section: Discussionmentioning
confidence: 99%
“…Because of previous treatment modalities (e.g. chemotherapy, steroids, and inactivity), a significant percentage of these patients already suffer from diminished physical function prior to transplantation …”
Section: Introductionmentioning
confidence: 99%
“…A major question that remains is the functional and quality of life implications of the residual mild‐to‐moderate neuropathy seen in these populations. Overall motor function, and specifically balance performance, has been shown to be impaired in children during and soon after non‐CNS cancer treatment . Adult survivors of childhood cancer also display neuromuscular deficits, in part due to chemotherapy exposure, that are associated with decreased physical performance .…”
Section: Discussionmentioning
confidence: 99%
“…Overall motor function, and specifically balance performance, has been shown to be impaired in children during and soon after non-CNS cancer treatment. [17][18][19][20] Adult survivors of childhood cancer also display neuromuscular deficits, in part due to chemotherapy exposure, that are associated with decreased physical performance. 2,3 In our own research, we have found that children on treatment have both balance and gait pattern deficits associated with CIPN.…”
Section: Discussionmentioning
confidence: 99%
“…Physical function testing in children with cancer is gaining increasing interest as reports of physical function impairment during and after treatment become more prevalent. Function disabilities include reductions in cardiopulmonary function, muscle strength, balance, and general physical weakness, that impact quality of life . The existing topic‐related studies include limited numbers of children (n = 15–128) as well as restricted diagnostic groups and inclusion criteria.…”
Section: Introductionmentioning
confidence: 99%